Gambaran umum koperasi modern dalam upaya adaptasi perkembangan teknologi digital di koperasi - Udin Hidayat (STIE Bangkinang Publishing, 2023)
This study aims to further examine the development of modern cooperatives from the perspective of a data scientist. The research method used is qualitative. The data analysis method used is by reducing data, presenting data, and finally drawing conclusions, withdrawing, or verifying. The results of this study conclude that conventional cooperatives in Indonesia actually have great potential to be modernized and have received attention from various parties. Strengthened by the existence of cooperation for the acceleration of modern cooperatives and also supported by the results of research conducted by several campuses or other journal sources. As a result, it is said that in this digital era, the digitalization of cooperatives is becoming increasingly important. However, in modern cooperatives, there are still many people who are confused because modern cooperatives use digital platforms. To overcome this, introduction, guidance, and counseling regarding digital-based modern cooperatives can be carried out by cooperative members and other parties.